2019
DOI: 10.1021/acs.iecr.8b04517
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodeoxygenation of Guaiacol Catalyzed by High-Loading Ni Catalysts Supported on SiO2–TiO2 Binary Oxides

Abstract: A series of SiO2–TiO2 binary oxides supported high loading Ni catalysts were prepared using the co-precipitation method and tested in guaiacol hydrodeoxygenation (HDO). The catalysts were characterized using N2 adsorption–desorption, XRD, TEM, FT-IR, XPS, H2-TPD, and NH3-TPD. The formation of Si–O–Ti bond in the SiO2–TiO2 binary oxides was verified by XPS, which can increase the total amount of acidic sites and enhance the interaction between metal Ni and TiO2. The oxygen defect sites of TiO2 were formed near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 57 publications
1
31
1
Order By: Relevance
“…In other words, chain segments or 'clusters' composed of pure phases are, on average, q 1/ larger than in the random mixture. The transition matrix (7) gives the stationary distributions of O environments (6).…”
Section: Simple Partial Phase Separation Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, chain segments or 'clusters' composed of pure phases are, on average, q 1/ larger than in the random mixture. The transition matrix (7) gives the stationary distributions of O environments (6).…”
Section: Simple Partial Phase Separation Modelsmentioning
confidence: 99%
“…The mixed TiO 2 -SiO 2 oxides have attracted considerable attention in the area of photocatalysis as it has been shown that they are more active than pure TiO 2 [1][2][3]. The mixed oxides serve as base components for complex nanomaterials with applications in photoluminescence [4], electrochemical sensors [5] or catalytic hydrogenation [6] dehydrogenation [7] and hydrodeoxygenation [8]. There are also multiple possible optical application for those coatings [9], with demonstrated use in waveguides [10,11], laser mirrors [12] and rugate filters [13].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies used catalysts combining noble and transition metals, such as supported Rh-Co in the HDO of anisole and biodiesel [4] or Ru-Fe in supported ionic liquid phase catalysts in HDO of aromatic substrates containing carbonyl groups [16]. However, noble metals are expensive, and hence their replacement by other transition metals is desired [4,8] and was thoroughly investigated [3,8,10,[17][18][19][20][21][22][23][24]. Another beneficial effect of transition-metal catalysts is that complete hydrogenation of the oxygenated compounds is avoided [3,10].…”
Section: Introductionmentioning
confidence: 99%
“…High conversions were obtained for all catalysts (80-97 %) with selectivities to HDO up to 97%. Other tested catalysts were molybdenum nitrides [17], Mo2C [22], copper chromite [3], Ni-Fe/SiO2 [19], Ni-Fe/γ-Al2O3 [18], Ni-Mo/γ-Al2O3 [24], NiFe alloys [21], supported Ni catalysts [20,23]. Mixed oxides catalysts containing copper are interesting for HDO reactions due to their high activity in hydrogenolysis and low tendency towards complete hydrogenation of the substrates [3].…”
Section: Introductionmentioning
confidence: 99%
“…Among these nonprecious metal catalysts (Co (Han et al, 2019), Mo (Yang et al, 2019), Ni, etc. ), nickel-based (Qiu et al, 2016;Zhang et al, 2018;Lu et al, 2019;Resende et al, 2019;Li et al, 2020;Shafaghat et al, 2020;Song et al, 2020) catalysts have been extensively studied for the hydrodeoxygenation of different biooil model compounds. Therefore, nonprecious metal catalysts represented by nickel-based catalysts have attracted much attention because of their high hydrogenation activity and low cost.…”
Section: Introductionmentioning
confidence: 99%